A SENSORY READING OF SPATIAL EXPERIENCE FROM A FILM'S SETTING - Ghina Shofia; Arnis Rochma Harani (Jurnal Arsitektur ARCADE, 2024)
Abstract: The purpose of this article is to explore spatial experience through the lens of film settings. Films have been structured to depict a narrative about a space and its experiences to date. There have been few studies examining how a spatial setting in a film can evoke an architectural experience. Through the analysis of sensory-centered experiences derived from spatial settings in films, this paper aims to contribute to the understanding of architecture, particularly the relationship between the body and the space. Using a qualitative approach, this article discusses the film "Later We Tell About Today" (NKCTHI) through a case study. The spaces that are the settings in this film can be viewed as the user's experience of space. Based on the findings of this study, users' spatial experiences are influenced by the four senses of sight, smell, hearing, and touch. As a result of the degradation of lighting, users usually feel a change in their experience of space through the sense of sight, from initially being focused with high concentration to being visually uncomfortable and feeling alert. Using spatial reading methods, this article demonstrates that residents in film settings experience a variety of spatial experiences..Keywords:, Spatial experience, sense, atmosphere, spatial setting, sensoryAbstrak: Tulisan ini bertujuan untuk membaca spatial experience melalui penelusuran menggunakan setting film. Selama ini film disusun untuk menunjukkan adanya narasi mengenai suatu ruang dan pengalamannya. Belum banyak yang mencoba untuk mempelajari bagaimana suatu setting ruang dalam film dapat memberikan pengalaman arsitektur. Tulisan ini mencoba memperluas pemahaman experience yang berpusat pada sensori dari setting ruang dalam film, ini berpotensi memperkaya pengetahuan arsitektur khususnya hubungan antara body dan space. Artikel ini menggunakan metode kualitatif dengan pembahasan melalui studi kasus film yang berjudul â€œNanti Kita Cerita Tentang Hari Iniâ€ (NKCTHI). Ruang-ruang yang menjadi setting tempat dalam film ini dapat dibaca sebagai pengalaman ruang penggunanya. Penelitian ini menunjukkan bahwa pengalaman ruang yang dirasakan oleh pengguna terkait dengan empat indra manusia sebagai pemicunya, yaitu penglihatan, penciuman, pendengaran, serta peraba. Melalui indra penglihatan, pengguna merasakan perubahan pengalaman ruang yang awalnya fokus dengan konsentrasi tinggi beralih menjadi ketidaknyamanan visual dan rasa waspada karena pengaruh degradasi pencahayaan. Tulisan ini menunjukkan adanya berbagai bentuk pengalaman ruang yang dirasakan penghuni pada setting film berbasis dari pembacaan ruang.Kata Kunci: ruang, pengalaman ruang, indra manusia